Study of Thermal Comfort in Traditional House Buildings (Case Study: Simalungun Traditional House) - Vinky Rahman; Luqman Hadi Wibowo (Talenta Publisher, 2021)
Abstract. Traditional houses were formed over a long period and are believed to be hereditary responsive to the surrounding physical and socio-cultural environment. Traditional Architecture is a building whose shape, decoration and method of implementation are passed down from generation to generation. Traditional architecture is a reflection of the values and culture that the community has interpreted. The adaptation of residents in the house is carried out by optimizing the positive potential of the surrounding environment and minimizing disturbances related to the comfort of living. The research problem is how the level of thermal comfort in the traditional house of Simalungun. The purpose of this study is to analyze the thermal comfort of the study object of the Simalungun traditional house. To determine the thermal conditions inside and outside the building, Measurements of temperature and humidity were carried out. Measurement data were analyzed and compared with Ecotech simulation data. The results of research carried out directly and simulating using Ecotech. This Simalungun traditional house can be categorized as having optimal comfort in terms of its physical physiological aspects and simulate using Ecotech simulations. As for the benefits of the research, it is hoped that it can provide knowledge about the thermal comfort of traditional houses, especially the traditional houses of Simalungun.